Directive and Expressive Speech Acts in Nadine Labaki's Capernaum (A Pragmatic Study) - Ifaqoh, Hanifah Insani; Su'aidi, Agus Ahmad (Islah: Journal of Islamic Literature and History, 2023)
This research is intended to present the forms and functions of directive speech acts and expressive speech acts. This research is entitled "Directive and Expressive Speech Acts in Capernaum Movie by Nadine Labaki (A Pragmatic Study)". This research employs a qualitative descriptive research method. The main data source is Capernaum movie while the secondary data sources are journals, articles, books, and other references. The data collection technique was performed by free listening technique, note-taking technique, and systematic observation technique. The result of this research is 119 dialogs. There were 82 dialogs in Capernaum presenting directive speech acts followed by 37 dialogs in Capernaum showing expressive speech acts. Based on the results, the researchers concludes that in the movie Capernaum there are directive speech acts and expressive speech acts.